2000
DOI: 10.1016/s0924-9338(00)00520-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychoactive drugs and neuroleptics on language in normal subjects and schizophrenic patients: a review

Abstract: The aim of this survey is to present an overview of research into psychopharmacology as regards the effects of different psychoactive drugs and neuroleptics (NL) on language in normal subjects and schizophrenic patients. Eighteen studies that have investigated the effects of different drugs (alcohol, amphetamines, secobarbital, L-dopa, psilocybin, ketamine, fenfluramine) and neuroleptics (conventional and atypical) on language are reviewed. There are no studies concerning the effects of neuroleptics on languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 44 publications
1
2
0
3
Order By: Relevance
“…Chenery et al (2004) revealed an absence of priming for the RU condition in schizophrenia, despite priming for the UR and RR conditions. Accordingly, this result may be consistent with the alterations to dopaminergic activity reported in this population (see Salome, Boyer, & Fayol, 2000, for a review). Similarly, changes to dopaminergic activity in schizophrenia may also account for findings of an increased spreading of activation during semantic priming tasks (e.g., Moritz et al, 2001; Spitzer, Braun, Maier, Hermle, & Maher, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Chenery et al (2004) revealed an absence of priming for the RU condition in schizophrenia, despite priming for the UR and RR conditions. Accordingly, this result may be consistent with the alterations to dopaminergic activity reported in this population (see Salome, Boyer, & Fayol, 2000, for a review). Similarly, changes to dopaminergic activity in schizophrenia may also account for findings of an increased spreading of activation during semantic priming tasks (e.g., Moritz et al, 2001; Spitzer, Braun, Maier, Hermle, & Maher, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Others have described several of these cognitive and physiological symptoms after ketamine and have speculated about their association with schizophrenia symptoms (Adler et al, 1999;Salomé et al, 2000;Krystal et al, 2003).…”
Section: Biological Theories Of Schizophrenia and Their Relation To Lmentioning
confidence: 99%
“…например, Кибрик, Подлесская, 2009). В то же время речь человека может изменяться и в течение небольшого отрезка времени под влиянием эмоций Сидоров, Филатова, 2012), после принятия психоактивных веществ (Salomé et al, 2000;Сухих, 2006), при сильном стрессе или от усталости.…”
Section: Introductionunclassified